Multivariable analysis : an introduction - Feinstein, Alvan R., 1925-2001 (Yale University Press, 1996)
For physicians, nurses, and all others who confront increasingly complex statistical methods in research, Dr. Alvan R. Feinstein offers welcome help. He has written a highly readable explanation of the uses and significance of multivariable analysis in medical and life science research. A physician with wide experience in both clinical work and research, Dr. Feinstein succeeds in demystifying arcane vocabulary and unfamiliar mathematics. His book is a roadmap taking the reader from the basics of univariate and bivariate statistics, through methods of converting information into data coded for computers, and on to multivariable statistics. Dr. Feinstein focuses on four methods common in the medical literature: multiple linear regression, multiple logistic regression, discriminant function analysis, and Cox regression. He also discusses such new methods as recursive partitioning and conjunctive consolidation. Clarifying examples and illustrations abound, and an accompanying floppy disk helps to facilitate learning.